2008
DOI: 10.1186/1478-4505-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Medicines coverage and community-based health insurance in low-income countries

Abstract: ObjectivesThe 2004 International Conference on Improving Use of Medicines recommended that emerging and expanding health insurances in low-income countries focus on improving access to and use of medicines. In recent years, Community-based Health Insurance (CHI) schemes have multiplied, with mounting evidence of their positive effects on financial protection and resource mobilization for healthcare in poor settings. Using literature review and qualitative interviews, this paper investigates whether and how CHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 35 publications
(26 reference statements)
2
37
0
2
Order By: Relevance
“…Although the national public health system is responsible for most of the total medication expenditure, especially for poor people, a population-based study conducted in Florianópolis, Santa Catarina, showed that 3.1% of the richest people allocate more than 15% of their income to the purchase of medicines, whereas this frequency is 9.6% among the poorest 3 . In agreement with this result, a systematic review demonstrated that the financial impact of the purchase of medicines on the household budget is greater among low-income people 2 . With respect to leisure-time physical activity, this scenario is not different.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although the national public health system is responsible for most of the total medication expenditure, especially for poor people, a population-based study conducted in Florianópolis, Santa Catarina, showed that 3.1% of the richest people allocate more than 15% of their income to the purchase of medicines, whereas this frequency is 9.6% among the poorest 3 . In agreement with this result, a systematic review demonstrated that the financial impact of the purchase of medicines on the household budget is greater among low-income people 2 . With respect to leisure-time physical activity, this scenario is not different.…”
Section: Discussionsupporting
confidence: 57%
“…This scenario is a matter of concern especially among individuals of low socioeconomic status, since expenses with medicines account for most of their private health expenditure. Furthermore, medication spending as a share of total expenditure on health is inversely proportional to income 2 . This scenario tends to increase health inequalities, with consequent health and even greater socioeconomic risks for poorer families 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The medicines' weight in the total health expenditures is inversely proportional to income, according to a literature review in 54 low-income countries. 16 Similarly, medicines have had the largest share of responsibility for health expenditures in Brazil, reaching approximately 47% of the total expenditures. 3 Income committed to drug expenditure, especially when it is not planned, can lead families to even greater health risks, like the reduction in the purchase of food products, and make them become more susceptible to health problems, or, by the economic order, make families become poorer or even indigent.…”
Section: Introductionmentioning
confidence: 99%
“…Entre os setores mais pobres da população, o dispêndio com medicamentos representa a maior parcela dos gastos privados em saúde, e estes gastos se dão de maneira inversamente proporcional à renda, conforme revisão da literatura em 54 países de baixa renda 22,25 .…”
Section: Discussionunclassified